KLASIFIKASI GENOTIP JAGUNG LOKAL ASAL KABUPATEN WAKATOBI DAN KABUPATEN BOMBANA BERDASARKAN KARAKTER FENOTIPNYA - Safuan, La Ode; Hadini, Hamirul (Jurnal Agroteknos, 2012)
The aims of the research were : (1) as resources of morfology data base of local corn of Southeast Sulawesi, and (2) to Classify local corn of Southeast Sulawesi based on fenotypic characters. The research was carried out at Poasia Vilage, District Rahandouna, Kendari, Southeast Sulawesi, from June to September 2011. The study was arranged on Randomized Block Desing (RBD), with  3  replicates.  The  treatment was  local  corn  varieties. Variabel measured were: cob height (cm)   plant height (cm), leaf number per plant, stem diameter (mm), cob length (cm), cob diametter (mm), row number on the cob, seed number on the cob, seed number on the row,   seed weight per cob, weight of 100 seed, production per hectar. Data were analysed using ANOVA,   multivariat PCA and Cluster Analysis with SAS Software. Result of the Research showed that : (1) analysis of variance, Principal Component Analysis, and cluster analysis showed consistent grouping based on    stem and leaf component, cob component, seed component, and production component, and (2) most of corn collection (30 cultivars) had moderate production capability (± 3 tons/ha), 11 cultivars had low production (1.76 to 2.48 tons/ha), and only 4 cultivars (AWT-06, BMB-02, BMB-03 and BMB-04) had high production and moderate age (± 90 days), reaching 4.14 to 4.75 tons/ha. Key Words : genotipe, local corn, caracter, clasification